"English Food" Project - Innovative lessons from the pandemic and sustainability - Labanca, Renata Adriana (Seven Editora, 2024)
The "English Food" project started as an online activity in the first year of the Covid 19 Pandemic. In the first and second year, we focus on the discussion of several articles on food science, these discussions take place in the English language. At the end of each month we invite a speaker to talk about the topic studied. We also began to explore how the pandemic was affecting the food industry and the lives of project participants in general. We discussed about new trends, such as the rise of food delivery services and the popularity of meal kits. Now, our focus has shifted to sustainability. We investigate how the food industry is responding to the climate crisis, exploring topics such as sustainable agriculture, waste reduction, and plant-based diets. We have also started to discuss the SDGs. SDGs is the acronym for Sustainable Development Goals, a global agenda adopted during the United Nations Summit on Sustainable Development in September 2015. The SDGs address global actions in the areas of poverty eradication, food security, agriculture, health, education, gender equality, reduced inequalities, energy, water and sanitation, sustainable production and consumption patterns, climate change, sustainable cities, protection and sustainable use of oceans and terrestrial ecosystems, inclusive economic growth, infrastructure, industrialization, among others. In short, the "English Food" project has been a journey of learning and adaptation. Through this project, we not only explore food science and emerging trends in the food industry, but also address critical sustainability issues and the United Nations Sustainable Development Goals. This project highlighted the importance of adaptability in times of change and the need to consider sustainability in all areas of our lives. By doing so, we hope to inspire others to do the same and contribute to a more sustainable future. After all, every little action counts, and together, we can make a difference, all while practicing English. DOI:https://doi.org/10.56238/sevened2024.007-027